2021
DOI: 10.1111/and.14242
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates endocrine dysfunction and defective sperm integrity associated with high‐fat diet‐induced obesity in male Wistar rats

Abstract: Obesity is a metabolic dysfunction triggered by refined carbohydrate and high-fat-rich foods, as well as sedentary lifestyle. It can also be as a result of increased calorie intake and reduced calorie expenditure mediated through environmental, genetic, epigenetic and neuropsychological factors (Castro et al., 2017;Leisegang et al., 2019). It is usually characterised by increased visceral adiposity (Agarwal et al., 2018). Obesity has become an epidemic in recent decades, with millions of people worldwide suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…HDF is also associated with dysfunction of the endocrine glands. In this regard, melatonin can alleviate spermatogenesis and steroidogenesis disorders caused by HDF‐related obesity by affecting hypothalamic–pituitary‐gonadal axis function (Oladele et al, 2022).…”
Section: Melatonin and Signalling Pathwaysmentioning
confidence: 99%
“…HDF is also associated with dysfunction of the endocrine glands. In this regard, melatonin can alleviate spermatogenesis and steroidogenesis disorders caused by HDF‐related obesity by affecting hypothalamic–pituitary‐gonadal axis function (Oladele et al, 2022).…”
Section: Melatonin and Signalling Pathwaysmentioning
confidence: 99%
“…This same pattern, however, was not observed in participants with inadequate consumption. This suggests a possible improvement in subclinical glucose tolerance, suppressed by the inflammatory status caused by the chronic misalignment inherent to chronic night work ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is highly correlated with a wide range of metabolic disease states, including metabolic disorders induced by a HFD. 38,39 Oxidative stress is a process in which free radicals, which are inadequately neutralized by antioxidants, cause cumulative damage, and this damage is aggravated by the reduced activity of antioxidative enzymes, such as SOD. 40 Numerous studies have reported that there are many sources of oxidative stress in animals fed a HFD.…”
Section: Discussionmentioning
confidence: 99%